Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To find the midpoint of the [tex]\( x \)[/tex]-intercepts of the function [tex]\( f(x) = (x-2)(x-4) \)[/tex], follow these steps:
1. Identify the [tex]\( x \)[/tex]-intercepts:
The [tex]\( x \)[/tex]-intercepts of a function occur where the function equals zero. To find them, we set [tex]\( f(x) = 0 \)[/tex] and solve the equation:
[tex]\[ (x - 2)(x - 4) = 0 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
This equation is satisfied when either [tex]\( x - 2 = 0 \)[/tex] or [tex]\( x - 4 = 0 \)[/tex]. Solving these:
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
So, the [tex]\( x \)[/tex]-intercepts are at [tex]\( x = 2 \)[/tex] and [tex]\( x = 4 \)[/tex].
3. Find the midpoint of the [tex]\( x \)[/tex]-intercepts:
To find the midpoint of these points, we use the midpoint formula for two points, [tex]\( x_1 \)[/tex] and [tex]\( x_2 \)[/tex], which is given by:
[tex]\[ \text{Midpoint} = \frac{x_1 + x_2}{2} \][/tex]
Here, [tex]\( x_1 = 2 \)[/tex] and [tex]\( x_2 = 4 \)[/tex]. Substituting these values into the formula:
[tex]\[ \text{Midpoint} = \frac{2 + 4}{2} = \frac{6}{2} = 3 \][/tex]
4. Result:
Therefore, the midpoint of the [tex]\( x \)[/tex]-intercepts is [tex]\( 3 \)[/tex].
Given the options provided, the correct answer is:
[tex]\[ (3,0) \][/tex]
1. Identify the [tex]\( x \)[/tex]-intercepts:
The [tex]\( x \)[/tex]-intercepts of a function occur where the function equals zero. To find them, we set [tex]\( f(x) = 0 \)[/tex] and solve the equation:
[tex]\[ (x - 2)(x - 4) = 0 \][/tex]
2. Solve for [tex]\( x \)[/tex]:
This equation is satisfied when either [tex]\( x - 2 = 0 \)[/tex] or [tex]\( x - 4 = 0 \)[/tex]. Solving these:
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
So, the [tex]\( x \)[/tex]-intercepts are at [tex]\( x = 2 \)[/tex] and [tex]\( x = 4 \)[/tex].
3. Find the midpoint of the [tex]\( x \)[/tex]-intercepts:
To find the midpoint of these points, we use the midpoint formula for two points, [tex]\( x_1 \)[/tex] and [tex]\( x_2 \)[/tex], which is given by:
[tex]\[ \text{Midpoint} = \frac{x_1 + x_2}{2} \][/tex]
Here, [tex]\( x_1 = 2 \)[/tex] and [tex]\( x_2 = 4 \)[/tex]. Substituting these values into the formula:
[tex]\[ \text{Midpoint} = \frac{2 + 4}{2} = \frac{6}{2} = 3 \][/tex]
4. Result:
Therefore, the midpoint of the [tex]\( x \)[/tex]-intercepts is [tex]\( 3 \)[/tex].
Given the options provided, the correct answer is:
[tex]\[ (3,0) \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.